2020
DOI: 10.1111/scd.12458
|View full text |Cite
|
Sign up to set email alerts
|

Nonsyndromic hereditary gingival fibromatosis: Characterization of a family and review of genetic etiology

Abstract: Our aim is to describe a family with a nonsyndromic form of hereditary gingival fibromatosis (HGF) and discuss genetic characteristics of this rare disease by reviewing reported cases.A mother and three descendants were diagnosed with HGF. There was marked variable expressivity: from severe generalized gingival overgrowth in a 16-year-old boy (the proband) to minimal manifestations in the mother. The proband was submitted to gingivectomy and gingivoplasty. In younger siblings, the disease remained stable for 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…HGF is genetically heterogeneous and ve subtypes are described corresponding to different candidate susceptibility loci, including gingival bromatosis Types 1-5 (GINGF1 to GINGF5) [42][43][44][45][46]. Besides, the son of sevenless-1 gene (SOS1, GINGF1) [42] and the RE1-silencing transcription factor gene (REST, GINGF5)[46, 47] were clearly associated with the occurrence of HGF [48,49]. Moreover, ALK, CD36, and ZNF862 (zinc nger protein 862) are new genes found recently, which are also associated with HGF [50,51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HGF is genetically heterogeneous and ve subtypes are described corresponding to different candidate susceptibility loci, including gingival bromatosis Types 1-5 (GINGF1 to GINGF5) [42][43][44][45][46]. Besides, the son of sevenless-1 gene (SOS1, GINGF1) [42] and the RE1-silencing transcription factor gene (REST, GINGF5)[46, 47] were clearly associated with the occurrence of HGF [48,49]. Moreover, ALK, CD36, and ZNF862 (zinc nger protein 862) are new genes found recently, which are also associated with HGF [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…This brosis is characterized by densely arranged collagen bundles, numerous broblasts, and connective tissue that is hyperkeratotic with elongated rete ridges and relatively avascular. Small calci ed particles, ulceration of the overlying mucosa, islands of osseous metaplasia, and in ammation can be occasionally observed [49,52]. Many studies have attempted to explore the pathogenesis of HGF currently, Gao Q et al found that KCNQ1, a member of the voltage-gated potassium channel family, played a critical role in the pathogenesis of HGF, promoted brogenic activity and facilitated extracellular matrix (ECM) synthesis and accumulation, and was upregulated in gingival tissues derived from HGF patients compared with normal gingival tissues, which may be a novel target for HGF therapy [53].…”
Section: Discussionmentioning
confidence: 99%
“…However, only two genes were clearly associated with the disease: son of sevenless-1 gene (SOS1; OMIM: 182530; GINGF1), identified by Hart et al in a Brazilian family, (4)and RE1-silencing transcription factor gene (REST; OMIM: 600571; GINGF5) described by Bayram et al (5)as the causal gene in three unrelated Turkish families. (2,3) The gingival growth usually begins at the time of eruption of the permanent dentition but also may develop with the eruption of the deciduous dentition, and rarely is present at birth. (6)Also, the presence of teeth appears to be necessary for that the development of HGF occurs because the condition usually disappears or recedes with loss of teeth.…”
Section: Fourth Casementioning
confidence: 99%
“…Hereditary gingival fibromatosis (HGF) is an inherited disease characterized by fibrous overgrowth with pathological, nonhemorrhagic, diffuse or focal, slowly progressive hyperplasia of the gingival tissue, resulting in fibromatous hyperplasia of the gingival tissue. 1 , 2 HGF was first reported by Goddard and Gross in 1856 and has a prevalence of one in 175,000 individuals. 3 , 4 Persistent gingival hyperplasia can lead to crowded dentition, inter-root interval, tooth displacement, and tooth eruption disorder, affecting the patient’s speech, difficulty in chewing, and aesthetics.…”
Section: Introductionmentioning
confidence: 99%